Methacrylic resin composition and molding

The methacrylic resin composition, formulated with specific ratios of methacrylic resin, internal lubricant, and fatty acid amide, addresses the challenges of reduced transparency and poor weather resistance in vehicle applications, achieving enhanced optical and mechanical properties.

JP2025076309APending Publication Date: 2025-05-15ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024173880
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-11-01
Filing Date
2024-10-02
Publication Date
2025-05-15

AI Technical Summary

Technical Problem

Existing methacrylic resin compositions for vehicle applications face challenges such as reduced transparency due to decreased total light transmittance and increased Haze, insufficient weather resistance, and poor jet blackness, especially when subjected to outdoor conditions.

Method used

A methacrylic resin composition comprising methacrylic resin, internal lubricant, and fatty acid amide, with specific mass ratios and content ranges, to achieve excellent transparency, scratch resistance, and jet blackness.

Benefits of technology

The composition provides improved total light transmittance, Haze, molding flowability, molding flow stability, heat deformation resistance, and scratch resistance when colored black, while maintaining cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025076309000007
    Figure 2025076309000007
  • Figure 2025076309000008
    Figure 2025076309000008
  • Figure 2025076309000001
    Figure 2025076309000001
Patent Text Reader

Abstract

To provide a methacrylic resin composition which can be a molding that has excellent total light transmittance, Haze, molding flowability, molding flow stability, heat-resistant moldability, and scratch resistance when colored in black, and exhibits high jet-blackness, and a production raw material thereof.SOLUTION: A methacrylic resin composition contains a methacrylic resin (A), an internal lubricant (B), and a fatty acid amide (C), wherein a percentage content of a methacrylate monomer unit in the methacrylic resin (A) is more than 85 pts.mass and 99.9 pts.mass or less; the internal lubricant (B) is one or more compounds selected from the group consisting of a fatty alcohol, butyl stearate, a metallic soap, a fatty acid, and a liquid paraffin; with respect to 100 pts.mass of the methacrylic resin (A), a mass ratio b of the internal lubricant (B) is from 0.05 to 0.6 pt.mass, and a mass ratio c of the fatty acid amide (C) is from 0.5 to 6 pts.mass; and the mass ratio b and the mass ratio c satisfy a specific relation.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a methacrylic resin composition and a molded article. [Background technology]

[0002] Methacrylic resins, such as polymethyl methacrylate (PMMA), are highly transparent and are therefore widely used in fields such as optical materials, vehicle parts, building materials, lenses, household goods, office equipment, lighting equipment, etc. In particular, their use is expanding in vehicle applications and in optical materials such as light guide plates and films for liquid crystal displays.

[0003] In particular, for automotive applications, molded products made of polycarbonate or ABS resin with hard coat treatment, or ASA or ABS resin with jet-black paint have been used for interior and exterior parts of automobiles. However, hard coat treatment (HC treatment) has problems such as defects and low productivity due to the occurrence of coating spots, and painting has problems such as volatile organic compounds (VOCs) contained in paint and energy costs incurred in the painting process. In addition, when material recycling or chemical recycling is performed on HC-treated products, the process of separating the coating layer is required, so recyclability is not good. In light of these problems, molded products that do not require HC treatment or painting are desired from the perspective of cost reduction, and replacement of resins with compounds has been actively studied in recent years. Here, the important properties are the scratch resistance and jet-blackness of the surface.

[0004] To impart these properties, for example, a method of mixing (compounding) additives into a thermoplastic resin has long been used. In recent years, methacrylic resins have come to be used mainly as thermoplastic resins. This is because methacrylic resins have excellent weather resistance and the highest surface pencil hardness and scratch resistance of all resins. In addition, because they have high transparency, they can produce deep and good coloring in molded products, especially when used as a replacement for painting.

[0005] However, in applications where high surface requirements are imposed, even methacrylic resins cannot withstand various abrasion phenomena, and are often subjected to HC treatment. As a method for solving this problem, for example, Patent Document 1 proposes a technology for improving mechanical properties and scratch resistance by incorporating a graft copolymer containing a silicone component and a fatty acid compound. In addition, Patent Document 2 proposes a technology for improving scratch resistance with excellent gloss and color development by incorporating an organic modified silicone and a fatty acid amide. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2022 / 085801 [Patent Document 2] International Publication No. 2018 / 016473 Summary of the Invention [Problem to be solved by the invention]

[0007] In Patent Document 1, mechanical properties and scratch resistance are improved by incorporating a graft copolymer containing a silicone component and a fatty acid compound, but the transparency is not good due to the effects of a decrease in total light transmittance and an increase in haze. It is not suitable for applications requiring jet blackness in particular. In addition, since it contains a rubber component, it has insufficient weather resistance and is prone to deterioration, especially in outdoor applications.

[0008] In Patent Document 2, the combined use of organic modified silicone and fatty acid amide provides excellent gloss and color development, and improves scratch resistance, but the inclusion of organic modified silicone reduces the total light transmittance of the molded product itself and increases haze, resulting in insufficient transparency, and there is room for improvement in jet blackness when made into a jet black material. In addition, depending on the content of organic modified silicone, a molded product may have poor appearance, such as a thin film peeling off. Furthermore, since the cost of organic modified silicones is generally high, there is a strong demand for materials that can be produced at low cost.

[0009] In view of the above-mentioned problems in the conventional art, the present invention aims to provide a molded article having excellent total light transmittance, haze, molding fluidity, molding flow stability, heat distortion resistance, and scratch resistance when colored black, and exhibiting high jet-black color, and a methacrylic resin composition which can be used as a raw material for producing the molded article. [Means for solving the problem]

[0010] As a result of intensive research to solve the above problems, the inventors discovered that the above problems can be solved by containing a methacrylic resin, an internal lubricant, and a fatty acid amide in a specific ratio, and thus completed the present invention.

[0011] That is, the present invention is as follows. [1] Contains methacrylic resin (A), internal lubricant (B), and fatty acid amide (C), The content of methacrylic acid ester monomer units in the methacrylic resin (A) is more than 85 parts by mass and 99.9 parts by mass or less, the internal lubricant (B) is one or more compounds selected from the group consisting of aliphatic alcohols, aliphatic alkyls, metal soaps, fatty acids, and liquid paraffin; a mass ratio b of the internal lubricant (B) is 0.05 to 0.6 parts by mass, and a mass ratio c of the fatty acid amide (C) is 0.5 to 6 parts by mass, relative to 100 parts by mass of the methacrylic resin (A), and the mass ratio b (parts by mass) and the mass ratio c (parts by mass) satisfy the following formulas (i) and (ii); A methacrylic resin composition comprising: 0.025≦b / c≦0.3 (i) c+b≦6.15 (ii) [2] The methacrylic resin composition according to [1], wherein the methacrylic acid ester monomer unit in the methacrylic resin (A) is a methyl methacrylate monomer unit. [3] The methacrylic resin composition according to [1] or [2], wherein the internal lubricant (B) is an aliphatic alcohol having 12 to 22 carbon atoms. [4] The methacrylic resin composition according to any one of [1] to [3], wherein the aliphatic amide (C) contains at least one aliphatic amide having 16 to 24 carbon atoms. [5] The methacrylic resin composition according to any one of [1] to [4], wherein when a molded article having a thickness of 3 mm is molded using a mold having a polishing grit of 8000 at a molding temperature of 260°C and a mold temperature of 60°C, the lightness L* of the molded article measured using a D65 light source, an SCE method, and a 10-degree visual field reflection mode is 1 or less. [6] The methacrylic resin composition according to any one of [1] to [5], further comprising a dye (D) including at least one dye selected from the group consisting of red dyes, yellow dyes, green dyes, blue dyes, and violet dyes. [7] The methacrylic resin composition according to [6], wherein the dye (D) contains one or more dyes selected from the group consisting of anthraquinone dyes, heterocyclic compound dyes, and perinone dyes. [8] The methacrylic resin composition according to any one of [1] to [7], which has a Vicat softening temperature of 95 to 108°C according to ISO306 B50 method. [9] The methacrylic resin composition according to any one of [1] to [8], wherein the average melt mass flow rate (MFR) of the second to sixth samples taken every 30 seconds at 230°C, a load of 3.8 kgf, and a pre-heating time of 4 minutes is 2.4 to 8.0 g / 10 min, and the absolute value of the difference in MFR between the second and sixth samples is less than 0.2 g / 10 min.

[10] A molded article comprising the methacrylic resin composition according to any one of [1] to [9].

[11] The molded article according to

[10] , which is a vehicle component. Effect of the Invention

[0012] According to the present invention, it is possible to provide a molded product which has excellent total light transmittance, haze, molding fluidity, molding flow stability, heat distortion resistance, and scratch resistance when colored black, and exhibits high jet-black color, and a methacrylic resin composition which can be used as a raw material for producing the molded product. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram illustrating a method for evaluating scratch resistance in the examples. [Diagram 2] FIG. 2 is a schematic diagram illustrating a molded body used in the evaluation of the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment for carrying out the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. The present embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out with appropriate modifications within the scope of its gist.

[0015] [Methacrylic resin composition] The methacrylic resin composition of the present embodiment comprises a methacrylic resin (A), an internal lubricant (B), and a fatty acid amide (C), the content of methacrylic acid ester monomer units in the methacrylic resin (A) is greater than 85 parts by mass and not more than 99.9 parts by mass, the internal lubricant (B) is one or more compounds selected from the group consisting of aliphatic alcohols, aliphatic alkyls, metal soaps, fatty acids, and liquid paraffin, the mass ratio b of the internal lubricant (B) is 0.05 to 0.6 parts by mass, and the mass ratio c of the fatty acid amide (C) is 0.5 to 6 parts by mass relative to 100 parts by mass of the methacrylic resin (A), and the mass ratio b (parts by mass) and the mass ratio c (parts by mass) satisfy the following formulas (i) and (ii). 0.025≦b / c≦0.3 (i) c+b≦6.15 (ii) The methacrylic resin composition of the present embodiment may be a composition consisting of only the methacrylic resin (A), the internal lubricant (B), and the fatty acid amide (C), or may further contain a dye (D) and other components. In this specification, a monomer component before polymerization is referred to as a "monomer" and may be abbreviated to "monomer". A structural unit constituting a polymer is referred to as a "monomer unit" and may be simply written as a "unit".

[0016] Hereinafter, each component constituting the resin composition of the present embodiment will be described.

[0017] (Methacrylic resin (A)) The methacrylic resin (A) in the present invention is a copolymer containing a structural unit derived from a methacrylic acid ester monomer (also referred to simply as a "methacrylic acid ester monomer unit" in this specification) and a structural unit derived from another vinyl monomer copolymerizable with the methacrylic acid ester monomer (also referred to simply as an "other vinyl monomer unit" in this specification). The methacrylic resin (A) may be one type of methacrylic resin or a mixture of multiple types of methacrylic resins.

[0018] -Methacrylic acid ester monomer- The methacrylic acid ester monomer forming the methacrylic acid ester monomer unit constituting the above-mentioned methacrylic resin is not particularly limited as long as it can achieve the effects of the present invention. Preferred examples include monomers represented by the following general formula (I): [ka] (In general formula (I), R3 represents a hydrocarbon group having 1 to 18 carbon atoms, and a hydrogen atom on the carbon of the hydrocarbon group may be substituted with a hydroxyl group or a halogen group.)

[0019] The above-mentioned methacrylic acid ester monomer is not particularly limited, but examples thereof include methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, 2-ethylhexyl methacrylate, t-butylcyclohexyl methacrylate, benzyl methacrylate, and 2,2,2-trifluoroethyl methacrylate. Among these, from the viewpoint of ease of handling and availability, methyl methacrylate, ethyl methacrylate, and propyl methacrylate are more preferred, and methyl methacrylate is particularly preferred. The above-mentioned methacrylic acid ester monomer may be used alone or in combination of two or more.

[0020] When the methacrylic resin is a copolymer, the mass ratio of the methacrylic acid ester monomer unit is more than 85 parts by mass and not more than 99.9 parts by mass, more preferably 85 to 99 parts by mass, even more preferably 90 to 98 parts by mass, even more preferably 95 to 98 parts by mass, and particularly preferably 97 to 98 parts by mass, relative to 100 parts by mass of the methacrylic resin. By having the mass ratio of the methacrylic acid ester monomer unit exceed 85 parts by mass, the heat resistance is further improved, and the resin can be suitably used for applications such as black coloring and absorbing solar heat. In addition, by having the content of the methacrylic acid ester monomer unit be 99.9 parts by mass or less, not only the flowability is further improved, but also the thermal decomposition resistance is improved, and the resin can be suitably molded in a member in which the appearance is important and the molding flow length is long and molded with a single gate.

[0021] -Other vinyl monomers- The other vinyl monomer (also referred to simply as "other vinyl monomer" in this specification) that forms another vinyl monomer unit copolymerizable with the methacrylic acid ester monomer that constitutes the above methacrylic resin is not particularly limited, but a preferred example is an acrylic acid ester monomer represented by the following general formula (II). [ka] (In general formula (II), R4 represents a hydrocarbon group having 1 to 18 carbon atoms, and a hydrogen atom on the carbon of the hydrocarbon group may be substituted with a hydroxyl group or a halogen group.)

[0022] The acrylic acid ester monomer is not particularly limited, but examples thereof include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, cyclohexyl acrylate, phenyl acrylate, 2-ethylhexyl acrylate, t-butylcyclohexyl acrylate, benzyl acrylate, 2,2,2-trifluoroethyl acrylate, etc. Among these, from the viewpoint of ease of handling and availability, methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, and isobutyl acrylate are more preferred, and methyl acrylate is particularly preferred from the viewpoint of not only excellent transparency and heat resistance of the polymer, but also easy reduction of remaining unreacted monomers.

[0023] In addition, examples of vinyl monomers other than the acrylic acid ester monomer represented by the general formula (II) that can be copolymerized with the methacrylic acid ester monomer include, but are not limited to, α,β-unsaturated acids such as acrylic acid and methacrylic acid; unsaturated group-containing divalent carboxylic acids and their alkyl esters such as maleic acid, fumaric acid, itaconic acid, and cinnamic acid; styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, and the like. Styrene monomers such as methylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, and isopropenylbenzene (α-methylstyrene); aromatic monomers such as 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, and isopropenyloctylbenzene. aromatic vinyl compounds; vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; unsaturated carboxylic anhydrides such as maleic anhydride and itaconic anhydride; maleimide, N-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, N-phenylmaleimide and N-cyclohexylmaleimide; amides such as acrylamide and methacrylamide; ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and other ethylene glycol or oligomers thereof, both terminal hydroxyl groups of which are esterified with acrylic acid or methacrylic acid; neopentyl glycol di(meth)acrylate, di(meth)acrylate, and other hydroxyl groups of two alcohols, both terminal hydroxyl groups of which are esterified with acrylic acid or methacrylic acid; trimethylolpropane, pentaerythritol, and other polyhydric alcohol derivatives, esterified with acrylic acid or methacrylic acid; and polyfunctional monomers such as divinylbenzene. The above other vinyl monomers may be used alone or in combination of two or more.

[0024] The mass ratio of the other vinyl monomer units is preferably 0.1 to 20 parts by mass, more preferably 0.1 to less than 15 parts by mass, even more preferably 1.0 to 15 parts by mass, even more preferably 1.5 to 7 parts by mass, still more preferably 2.0 to 5 parts by mass, and particularly preferably 2.0 to 3.0 parts by mass, relative to 100 parts by mass of the methacrylic resin. When the content of the other vinyl monomer units is 0.1 parts by mass or more, the flowability and thermal decomposition resistance tend to be further improved. Also, when the content of the other vinyl monomer units is 20 parts by mass or less, the heat resistance tends to be further improved.

[0025] In the above methacrylic resin, a vinyl monomer other than the vinyl monomers exemplified above may be appropriately added and copolymerized for the purpose of improving properties such as heat resistance and processability.

[0026] - Weight average molecular weight and molecular weight distribution of methacrylic resins - The weight average molecular weight and molecular weight distribution of the above methacrylic resin will now be described. The weight average molecular weight (Mw) of the methacrylic resin measured by gel permeation chromatography (GPC) is preferably 50000 to 300000. By having the weight average molecular weight of the methacrylic resin within the above range, the fluidity, mechanical strength, and solvent resistance can be balanced, and good molding processability tends to be maintained. In particular, from the viewpoint of obtaining excellent mechanical strength and solvent resistance, the weight average molecular weight (Mw) of the methacrylic resin is preferably 50000 or more, more preferably 60000 or more, even more preferably 70000 or more, even more preferably 80000 or more, and even more preferably 90000 or more. In addition, from the viewpoint of the methacrylic resin exhibiting good fluidity, the weight average molecular weight (Mw) of the methacrylic resin is preferably 300000 or less, more preferably 250000 or less, even more preferably 230000 or less, even more preferably 210000 or less, and even more preferably 180000 or less.

[0027] The molecular weight distribution (Mw / Mn) of the methacrylic resin is preferably 1.6 to 6.0, more preferably 1.7 to 5.0, even more preferably 1.8 to 5.0, and particularly preferably 1.8 to 2.3. When the molecular weight distribution of the methacrylic resin is within the above range, the balance between molding flow and mechanical strength tends to be excellent. Here, Mw represents the weight average molecular weight, and Mn represents the number average molecular weight.

[0028] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin can be measured by GPC, and can be measured by the method described in the examples below. Specifically, a calibration curve is created from the elution time and weight average molecular weight using a standard methacrylic resin with a known monodisperse weight average molecular weight and available as a reagent, and an analytical gel column that elutes high molecular weight components first, and then the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin to be measured can be obtained based on the obtained calibration curve. The molecular weight distribution can be calculated from the obtained weight average molecular weight (Mw) and number average molecular weight (Mn). The number average molecular weight (Mn) is a simple average of the molecular weight per molecule, and is defined as the total weight of the system / the number of molecules in the system. The weight average molecular weight (Mw) is defined as the average of the molecular weight by weight fraction.

[0029] - Proportion of molecular weight components with molecular weights of 1 / 5 or less of the peak top molecular weight (Mp) of methacrylic resin - From the viewpoint of solvent resistance and fluidity, the proportion of components having a molecular weight of 1 / 5 or less of the peak top molecular weight (Mp) obtained from the GPC elution curve of the methacrylic resin obtained by the GPC method is preferably 3 to 50%, more preferably 3 to 45%, and even more preferably 3 to 40% relative to the total area of ​​the GPC elution curve of the methacrylic resin. When the proportion of components having a molecular weight of 1 / 5 or less of the peak top molecular weight (Mp) is 3% or more, molding fluidity tends to be improved, and the molecular orientation of the molded product surface tends to be relaxed, resulting in good scratch resistance. In addition, when the proportion of components having a molecular weight of 1 / 5 or less of the peak top molecular weight (Mp) is 50% or less, solvent resistance tends to be improved. Here, "the percentage (%) of components having a molecular weight of 1 / 5 or less of the peak top molecular weight (Mp)" refers to the percentage of the area of ​​the area of ​​the GPC elution curve that corresponds to components having a molecular weight of 1 / 5 or less of the peak top molecular weight (Mp) when the total area of ​​the GPC elution curve is taken as 100%, and can be measured by the method described in the examples below. Note that "peak top molecular weight (Mp)" refers to the weight molecular weight that shows a peak in the GPC elution curve. When there are multiple peaks in the GPC elution curve, the molecular weight at the peak that shows the most abundant weight molecular weight is taken as the peak top molecular weight (Mp). It is preferable that the amount of methacrylic resin components having a weight molecular weight of 500 or less is as small as possible, since they cause a foam-like appearance defect called "silver" during molding.

[0030] -Methacrylic resin manufacturing method- The methacrylic resin can be produced by any one of bulk polymerization, solution polymerization, suspension polymerization, cast polymerization, and emulsion polymerization. Among these, from the viewpoint of obtaining a methacrylic resin with fewer impurities, bulk polymerization, solution polymerization, cast polymerization, and suspension polymerization are preferred, and from the viewpoint of the power energy used in polymerization determined by the balance between the polymerization temperature and the polymerization time, and from the viewpoint of heat removal stability, suspension polymerization is more preferred.

[0031] The polymerization temperature may be appropriately selected from the viewpoints of reducing unstable terminals and obtaining a methacrylic resin with higher thermal stability, and is preferably 50° C. or higher and 100° C. or lower, more preferably 60° C. or higher and 90° C. or lower.

[0032] When producing a methacrylic resin, a polymerization initiator may be used. The polymerization initiator is not particularly limited, but when performing radical polymerization, for example, di-t-butyl peroxide, lauroyl peroxide, decanoyl peroxide, stearyl peroxide, benzoyl peroxide, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, dilauroyl peroxide, dicumyl peroxide, t-butyl peroxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, cyclohexane peroxide, 2,5-di Examples of the initiator include organic peroxides such as methyl-2,5-di(benzoylperoxy)hexane and 1,1-bis(t-butylperoxy)cyclohexane; and general azo-based radical polymerization initiators such as azobisisobutyronitrile, azobisisovaleronitrile, 1,1-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis-4-methoxy-2,4-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, 2,2'-azobis-2-methylbutyronitrile, and 2-(carbamoylazo)isobutyronitrile. These initiators may be used alone or in combination of two or more. These radical initiators may be used in combination with a suitable reducing agent as a redox initiator.

[0033] These radical polymerization initiators and / or redox initiators are generally used in the range of 0 to 1 part by mass per 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin, and can be appropriately selected taking into consideration the temperature at which the polymerization is performed and the half-life of the polymerization initiator.

[0034] When selecting bulk polymerization, cast polymerization, or suspension polymerization as the polymerization method of methacrylic resin, from the viewpoint of preventing coloration of methacrylic resin, it is preferable to use organic peroxide as polymerization initiator to carry out polymerization.As such organic peroxide, the same as above can be mentioned, among which, lauroyl peroxide, decanoyl peroxide, and t-butylperoxy-2-ethylhexanoate are preferable, and lauroyl peroxide is more preferable.

[0035] When a methacrylic resin is polymerized by a solution polymerization method at a high temperature of 90° C. or higher, it is preferable to use an organic peroxide or azobis initiator, etc., which has a 10-hour half-life temperature of 80° C. or higher and is soluble in the organic solvent used, as a polymerization initiator. Examples of such organic peroxides and azobis initiators include those similar to those mentioned above, and among these, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, cyclohexane peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 1,1-azobis(1-cyclohexanecarbonitrile), 2-(carbamoylazo)isobutyronitrile, etc. are preferred.

[0036] When producing a methacrylic resin, the molecular weight of the methacrylic resin may be controlled as necessary. The method for controlling the molecular weight of the methacrylic resin is not particularly limited, but includes, for example, a method of changing the polymerization method or polymerization conditions, a method of selecting a polymerization initiator, a method of adjusting the amount of a chain transfer agent or an iniferter, etc. These molecular weight control methods may be used alone or in combination of two or more methods.

[0037] The iniferter is not particularly limited, but examples thereof include dithiocarbamates, triphenylmethylazobenzene, and tetraphenylethane derivatives.

[0038] The chain transfer agent is not particularly limited, but examples thereof include alkyl mercaptans, dimethylacetamide, dimethylformamide, triethylamine, etc. Among these, alkyl mercaptans are preferred from the viewpoint of handling and stability. The alkyl mercaptans are not particularly limited, but examples thereof include n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-tetradecyl mercaptan, n-octadecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane tris(thioglycolate), pentaerythritol tetrakis(thioglycolate), etc.

[0039] The chain transfer agent and the iniferter can be appropriately added according to the molecular weight of the target methacrylic resin, and the molecular weight can be adjusted by adjusting the amount of the chain transfer agent and the iniferter added. In general, they are used in the range of 0.001 parts by mass to 5 parts by mass with respect to 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin.

[0040] (Internal Lubricant (B)) The methacrylic resin composition contains one or more compounds selected from the group consisting of aliphatic alcohols, aliphatic alkyls, metal soaps, fatty acids, and liquid paraffin as an internal lubricant (B). The inclusion of the internal lubricant (B) reduces the residual stress on the surface, improving the scratch resistance of the methacrylic resin composition. From the viewpoint of preventing silver streaks from occurring during injection molding and preventing the transparency of the molded product from decreasing, it is more preferable to contain an aliphatic alcohol, and it is even more preferable that the aliphatic alcohol is 50% by mass or more of the total content of the internal lubricant (B), even more preferably that the aliphatic alcohol is 70% by mass or more of the total content of the internal lubricant (B), and it is particularly preferable that the aliphatic alcohol is 95% by mass or more of the total content of the internal lubricant (B). The internal lubricant (B) may be used alone or in combination of two or more kinds.

[0041] As the aliphatic alcohol, from the viewpoint of obtaining a good appearance when made into a methacrylic resin composition, aliphatic alcohols having 12 to 22 carbon atoms, such as lauryl alcohol, palmityl alcohol, stearyl alcohol, oleyl alcohol, arachidyl alcohol, behenyl alcohol, etc., are preferred, saturated aliphatic alcohols having 12 to 22 carbon atoms, such as lauryl alcohol, palmityl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, etc. are more preferred, and from the viewpoints of cost and ease of availability, saturated aliphatic alcohols having 16 to 22 carbon atoms, such as palmityl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, etc. are even more preferred.

[0042] The mass ratio of the internal lubricant (B) is preferably 0.01 parts by mass or more and 1.5 parts by mass or less, more preferably 0.03 parts by mass or more and 1 part by mass or less, even more preferably 0.05 parts by mass or more and 0.6 parts by mass or less, even more preferably 0.05 parts by mass or more and 0.5 parts by mass or less, even more preferably 0.05 parts by mass or more and 0.4 parts by mass or less, and particularly preferably 0.1 parts by mass or more and 0.3 parts by mass or less, relative to 100 parts by mass of the methacrylic resin (A). It is presumed that the amount of the internal lubricant (B) is 0.01 parts by mass or more, which tends to reduce the residual stress on the surface of the resin composition, and this contributes to improving the scratch resistance. In addition, since the resin pressure during injection molding is reduced, sink marks can be reduced in molded bodies having ribs, bosses, and snap fits, and a good appearance can be achieved. By the amount of the internal lubricant (B) being 1.5 parts by mass or less, it is possible to suppress the decrease in tensile strength properties due to excessive decrease in residual stress as a resin composition.

[0043] (Fatty acid amide (C)) The methacrylic resin composition contains the fatty acid amide (C), so that a molecular film is formed on the surface of the molded article, thereby improving the scratch resistance.

[0044] The fatty acid amide (C) is not limited to the following, but preferably contains at least one type of aliphatic amide having 16 to 24 carbon atoms, and more preferably is at least one type of aliphatic amide having 16 to 24 carbon atoms. The above-mentioned aliphatic amides preferably include one or more types having an amide group having 16 to 22 carbon atoms at the molecular terminal. Among these, stearamide, behenamide, oleamide, and erucamide are more preferable from the viewpoints of both excellent scratch resistance and jet-blackness, ease of availability, and cost. The fatty acid amide (C) may be used alone or in combination of two or more.

[0045] The purity of the fatty acid amide (C) is preferably 80 wt% or more, more preferably 85 wt% or more, in order to improve scratch resistance, and is preferably 95 wt% or less from the viewpoints of availability and cost.

[0046] The mass ratio of the fatty acid amide (C) is preferably 0.5 parts by mass or more and 6 parts by mass or less, more preferably 1 part by mass or more and 6 parts by mass or less, more preferably 1 part by mass or more and 4.5 parts by mass or less, more preferably 1.2 parts by mass or more and 4 parts by mass or less, even more preferably 1.5 parts by mass or more and 3.5 parts by mass or less, and particularly preferably 2 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the methacrylic resin (A). When the fatty acid amide (C) is 0.5 parts by mass or more, a sufficient molecular film is formed on the surface of the molded body, and the scratch resistance of the resin composition tends to be further improved. When the fatty acid amide (C) is 6 parts by mass or less, excellent total light transmittance and haze can be maintained, and bleeding during molding can be suppressed. In addition, excessive deterioration of heat resistance is prevented, and it can be suitably used for applications requiring heat resistance, such as automotive exterior design materials and automotive interior design materials.

[0047] In the methacrylic resin composition of this embodiment, when the mass ratio of the internal lubricant (B) to 100 parts by mass of the methacrylic resin (A) is b (parts by mass), and the mass ratio of the fatty acid amide (C) to 100 parts by mass of the methacrylic resin (A) is c (parts by mass), the following formulae (i) and (ii) are satisfied. 0.025≦b / c≦0.3 (i) c+b≦6.15 (ii)

[0048] In addition to imparting jet blackness and excellent scratch resistance when the molded body is colored black, b / c is preferably 0.025 to 0.3, more preferably 0.03 to 0.1, and even more preferably 0.03 to 0.088 in terms of improving scratch resistance immediately after molding (within 2 hours). It is presumed that by having b / c in the range of 0.025 to 0.3, a fatty acid amide molecular film can be efficiently formed. In addition, by having b / c of ​​0.025 or more, the resin pressure during injection molding tends to decrease, and in molded bodies having ribs, bosses, and snap fits, sink marks can be reduced and a good appearance can be achieved. In order to prevent mold staining and product staining due to excessive bleeding during molding, c+b is preferably 6.15 or less, more preferably 4.65 or less, and even more preferably 3.15 or less. By having c+b of 6.15 or less, the composition can be suitably used without impairing adhesive strength in applications such as pillar garnishes for automotive exterior decorative materials that are fixed with double-sided tape.

[0049] (Dye (D)) The methacrylic resin composition of the present embodiment may further contain a dye (D). The dye (D) preferably contains at least one dye selected from the group consisting of red dyes, yellow dyes, green dyes, blue dyes, and violet dyes, and more preferably contains at least one dye selected from the group consisting of red dyes, yellow dyes, green dyes, blue dyes, and violet dyes. The dye (D) may be used alone or in combination of two or more kinds.

[0050] In particular, when coloring in black, in order to increase the depth of the jet blackness, it is preferable that the dye (D) contains two or more dyes having different hues, more preferably three or more dyes having different hues, and even more preferably three or more dyes selected from the group consisting of red, yellow, green, blue and purple dyes. This is because, from the viewpoint of expressing a deeper jet blackness, it is preferable to express the jet blackness by a combination that evenly includes the three primary colors of light, rather than a narrow range of combinations such as a simple combination of only a blue dye and a yellow dye, or a combination of only a green dye and a red dye. Examples of such combinations include combinations of appropriate amounts of dyes from multiple dye systems, such as a combination of a purple dye, a green dye, a yellow dye, and a blue dye; a combination of a purple dye, a yellow dye, a green dye, and a red dye; and a combination of a red dye, a green dye, and a blue dye. Of these, the combination of a red dye, a green dye, a yellow dye, and a blue dye is preferred from the viewpoint that it is easier to achieve the desired jet black color because there are already many commercially available products and there are many types of lightfast dyes, which will be described later.

[0051] Examples of red dyes, as expressed by the color index, include Solvent Red 52, 111, 135, 145, 146, 149, 150, 151, 155, 179, 180, 181, 196, 197, 207, Disperse Red 22, 60, and 191. Examples of blue dyes, as expressed by the color index, include Solvent Blue 35, 45, 78, 83, 94, 97, 104, and 105. Examples of yellow dyes include Disperse Yellow 160, Disperse Yellow 54, Disperse Yellow 160, and Solvent Yellow 33, as expressed by the Color Index. Examples of green dyes include Solvent Green 3, 20, and 28, as expressed by the Color Index. Examples of purple dyes, as expressed by the Color Index, include Solvent Violet 28, 13, 31, 35, and 36. These dyes may be used alone or in combination of two or more for each color.

[0052] From the viewpoint of weather resistance, dye (D) preferably contains one or more dyes selected from the group consisting of anthraquinone dyes, heterocyclic compound dyes, and perinone dyes, and is preferably one or more dyes selected from the group consisting of anthraquinone dyes, heterocyclic compound dyes, and perinone dyes. Examples of anthraquinone dyes, as expressed by the Color Index, include Solvent Violet 36, Solvent Green 3, 28, Solvent Blue 94, 97, and Disperse Red 22. Examples of heterocyclic compound dyes, as expressed by the Color Index, include Disperse Yellow 160. Examples of perinone dyes, as expressed by the Color Index, include Solvent Red 179. Each of these may be used alone or in combination of two or more.

[0053] The mass ratio of the dye (D) is preferably 0.01 to 1.5 parts by mass, more preferably 0.02 to 1.0 parts by mass, even more preferably 0.03 to 0.8 parts by mass, and particularly preferably 0.05 to 0.6 parts by mass, based on 100 parts by mass of the methacrylic resin composition, from the viewpoints of weather resistance and raw material cost. By using 0.01 to 1.5 parts by mass of the dye (D), it is possible to adjust the L* to a predetermined range, as described below.

[0054] In order to effectively achieve light shielding even in a thin-walled molded article, the dye (D) preferably contains a dye having a maximum wavelength of 480 to 620 nm and a dye having a maximum wavelength of 600 to 760 nm within a wavelength range of 400 to 780 nm, and more preferably contains a dye having a maximum wavelength of 520 to 620 nm and a dye having a maximum wavelength of 640 to 740 nm. In addition, the wavelength at which the transmittance reaches 5% when the molded product is 3 mm thick is preferably 550 nm or more, more preferably 650 nm or more, even more preferably 700 nm or more, and particularly preferably 750 nm or more. By having a wavelength at which the transmittance reaches 5% when the molded product is 3 mm thick of 550 nm or more, it is possible to realize a good appearance when used in thin automotive exterior design materials and automotive interior design materials, even in environments where the material on the back side does not show through, even when the material is exposed to sunlight.

[0055] (Other Ingredients) The methacrylic resin composition of the present embodiment may contain various additives within the range not impairing the effects of the present invention. The other components are components other than the dye (D) described above.

[0056] Examples of the additives include antistatic agents such as polyethers, polyetheresters, polyetherester amides, alkylsulfonates, and alkylbenzenesulfonates, antioxidants, ultraviolet absorbers, stabilizers such as heat stabilizers and light stabilizers, flame retardants, flame retardant assistants, curing agents, curing accelerators, pigments made of inorganic metal compounds, conductivity imparting agents, stress relaxation agents, crystallization accelerators, hydrolysis inhibitors, impact imparting agents, compatibilizers, nucleating agents, reinforcing agents, reinforcing agents, flow adjusters, sensitizers, rubber polymers, thickeners, anti-settling agents, anti-sagging agents, fillers, defoamers, coupling agents, rust inhibitors, antibacterial and anti-fungal agents, antifouling agents, and conductive polymers. In particular, it is preferable to add a heat stabilizer, an ultraviolet absorber, a flame retardant, etc. for a wide range of indoor and outdoor applications. Furthermore, a rubber copolymer may be added as a stress relaxant or an impact imparting agent. From the viewpoint of maintaining good transparency, jet blackness when colored, scratch resistance, and bleed-out resistance, it is preferable not to add a high molecular weight substance other than the methacrylic resin (A) as an additional component. Examples of high molecular weight substances other than the methacrylic resin (A) include polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polycarbonate, ABS resin, AES resin, polysulfone, polyphenylene ether, polyarylate, polylactic acid, polyethersulfone, polyimide, polyetherimide, polyvinylpyrrolidone, polyacrylonitrile, thermoplastic elastomer, polyvinylidene fluoride, polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyamide, polyacetal, polyvinyl alcohol, silicone resin, polyphenylene sulfide, polyether ether ketone, etc. The resin component contained in the methacrylic resin composition of the present embodiment is preferably the above methacrylic resin (A) alone.

[0057] -Heat stabilizer- The heat stabilizer is not particularly limited, but examples thereof include hindered phenol-based antioxidants, phosphorus-based processing stabilizers, etc. Among these, hindered phenol-based antioxidants are preferred. Examples of such a heat stabilizer include, but are not limited to, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide, 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylene bis(oxadiphenyl ether), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione; 1,3,5-tris(4-tert-butyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione; butyl-3-hydroxy-2,6-xylin)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamine)phenol, etc., and pentaerythritol terakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is preferred. These may be used alone or in combination of two or more.

[0058] -Ultraviolet absorber- The ultraviolet absorbing agent is not particularly limited, and examples thereof include benzotriazole-based compounds, benzotriazine-based compounds, benzoate-based compounds, benzophenone-based compounds, oxybenzophenone-based compounds, phenol-based compounds, oxazole-based compounds, malonic acid ester-based compounds, cyanoacrylate-based compounds, lactone-based compounds, salicylic acid ester-based compounds, and benzoxazinone-based compounds. Among these, benzotriazole-based compounds and benzotriazine-based compounds are preferred. These may be used alone or in combination of two or more.

[0059] The vapor pressure (P) of the ultraviolet absorber at 20° C. is preferably 1.0×10 -4 Pa or less, more preferably 1.0×10 -6 Pa or less, and more preferably 1.0×10 -8 Pa or less. Here, "excellent moldability" means, for example, that the ultraviolet absorber adheres less to the mold surface during injection molding, or adheres less to the roll during film molding. If the ultraviolet absorber adheres to the roll, it will eventually adhere to the surface of the desired molded product, which may deteriorate the appearance and optical properties. Therefore, when the molded product is used as an optical material, it is particularly important that the moldability is excellent. The vapor pressure (P) of the ultraviolet absorber at 20°C is preferably closer to 0 Pa, since bleeding to the molded product surface is suppressed and it is more likely to remain in the molded product.

[0060] From the viewpoint of preventing bleed-out, the melting point (Tm) of the ultraviolet absorber is preferably 80° C. or higher, more preferably 100° C. or higher, even more preferably 130° C. or higher, and even more preferably 160° C. or higher.

[0061] The mass loss rate of the ultraviolet absorbent when the temperature is raised from 23°C to 260°C at a rate of 20°C / min is preferably as close to 0% as possible, and from the viewpoint of preventing bleed-out, the mass loss rate is preferably 0% or more and 50% or less, more preferably 30% or less, even more preferably 15% or less, even more preferably 10% or less, and still more preferably 5% or less.

[0062] -Flame retardants- The flame retardant is not particularly limited, but examples thereof include cyclic nitrogen compounds, phosphorus-based flame retardants, silicon-based flame retardants, cage-shaped silsesquioxanes or partially cleaved structures thereof, and silica-based flame retardants.

[0063] (Mass percentage) From the viewpoints of maintaining excellent transparency and preventing molding defects such as bleed-out, the mass proportion of the methacrylic resin (A) in the methacrylic resin composition is preferably 65 to 99.9 parts by mass, more preferably 75 to 99.9 parts by mass, and particularly preferably 95 to 99.9 parts by mass, per 100 parts by mass of the methacrylic resin composition.

[0064] The total mass ratio of the methacrylic resin (A), the internal lubricant (B) and the fatty acid amide (C) to 100 mass% of the methacrylic resin composition is preferably 90 mass% or more, more preferably 95 mass% or more, even more preferably 99.2 mass% or more, and still more preferably 99.7 mass% or more.

[0065] (Vicat Softening Temperature of Methacrylic Resin Composition) The methacrylic resin composition of this embodiment preferably has a Vicat softening temperature of 90°C or higher according to ISO306 B50. If the Vicat softening temperature is 90°C or higher, the methacrylic resin composition of this embodiment has sufficient heat distortion resistance even when used outdoors. In order to ensure suitability for applications such as vehicle components that are exposed to direct sunlight for long periods of time, and for applications that have joints with other components, the Vicat softening temperature is more preferably 95°C or higher, even more preferably 97°C or higher, even more preferably 100°C or higher, and particularly preferably 103°C or higher. Also, it is preferably 108°C or lower. The Vicat softening temperature can be adjusted by adjusting the molecular weight and composition of the methacrylic resin (A), the type, content and composition of the internal lubricant (B) and the fatty acid amide (C). More specifically, the Vicat softening temperature can be measured by the method described in the Examples below.

[0066] (Melt mass flow rate (MFR) of methacrylic resin composition) The methacrylic resin composition of the present embodiment preferably has an average MFR of 2.4 g / 10 min or more for the second to sixth samples taken at 230° C., 3.8 kgf load, 4 minutes preheating time, and every 30 seconds. The first sample taken tends to have a large error in the measured value due to the influence of air bubbles, etc., so the measured value for the second sample and thereafter is used. By having an MFR of 2.4 g / 10 min or more, it can be said that the composition has excellent molding fluidity that allows molding of even long members. In order to be suitably used for applications such as automotive pillar garnishes, rear garnishes, front garnishes, rear spoilers, slide rail covers, and front grilles that require particularly excellent fluidity, the MFR is more preferably 2.8 g / 10 min or more, and particularly preferably 3.1 g / 10 min or more. For the purpose of suppressing flash due to overpacking, the MFR is preferably 8.0 g / 10 min or less, more preferably 7.0 g / 10 min or less, and particularly preferably 6.0 g / 10 min or less. The MFR can be adjusted by adjusting the molecular weight of the methacrylic resin (A), the type, content, and composition of the internal lubricant (B) and the fatty acid amide (C). More specifically, the MFR can be measured by the method described in the Examples below.

[0067] (MFR stability of methacrylic resin composition) The methacrylic resin composition of this embodiment is preferably such that the absolute value of the difference in MFR (melt mass flow rate) between the sixth and second samples taken every 30 seconds at 230°C, a load of 3.8 kgf, and a preheating time of 4 minutes is 0.2 g / 10 min or less, more preferably less than 0.2 g / 10 min, and even more preferably 0.15 g / 10 min or less. The smaller the absolute value of the difference in MFR between the sixth and second samples, the less likely the fluidity will change due to heating caused by retention in the cylinder when the molding cycle becomes longer, and therefore stable molding can be performed, and a value of 0.2 g / 10 min or less tends to enable stable molding. Note that the measurement error of the first sample tends to be large due to the influence of air bubbles, etc., so the measurement value of the second sample is used. The stability of MFR tends to decrease when it contains elastomer components such as thermoplastic polyurethane, when it contains a large amount of additives that promote the decomposition of the resin, or when the methacrylic resin has a structure with many molecular ends, making stable molding difficult.On the other hand, it can be improved by using methacrylic resins with a structure with few molecular ends and additives that suppress the decomposition of the resin, such as heat stabilizers.

[0068] (Tensile stress of methacrylic resin composition) The methacrylic resin composition of the present embodiment preferably has a tensile stress of 70 MPa or more according to ISO 527. If the tensile stress is 70 MPa or more, the methacrylic resin composition of the present embodiment has sufficient strength even when used in applications involving joints with other members, such as vehicle members. The tensile stress is more preferably 73 MPa or more, and even more preferably 75 MPa or more. The tensile stress can be adjusted by adjusting the molecular weight and composition of the methacrylic resin (A), the type, content and composition of the internal lubricant (B) and fatty acid amide (C), and the contents of other resins and additive components. More specifically, the tensile stress can be measured by the method described in the Examples below.

[0069] When the methacrylic resin composition of the present embodiment is used as a transparent material, the total light transmittance at a thickness of 3 mm is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more, in accordance with JISK7361 (ISO13468). The closer the total light transmittance is to 100%, the better. When the total light transmittance is within the above range, visibility is improved when used for transparent applications, and a deep color can be produced when used for coloring applications. The total light transmittance of a typical resin composition is less than 100%. The total light transmittance can be measured by the method described in the examples described below.

[0070] The methacrylic resin composition of the present embodiment has a haze of preferably 6% or less, more preferably 1% or less, even more preferably 0.8% or less, and even more preferably 0.5% or less, when molded into a 3 mm thick article, as measured in accordance with JISK7136 (ISO14782). The closer the haze is to 0%, the better. If the haze is within the above range, a molded article having excellent visibility and transparency can be obtained when used for transparent applications, and a molded article having a color tone with excellent deep luster can be obtained when used for coloring applications. Haze can be measured by the method described in the Examples below.

[0071] (L* of resin composition) When the methacrylic resin composition of the present embodiment is used to mold a molded body having a thickness of 3 mm at a molding temperature of 260° C. and a mold temperature of 60° C. using a mold having a polishing number of 8000, the brightness L* of the molded body measured using a D65 light source and an SCE method 10-degree field of view reflection mode is preferably 1 or less. Since the brightness L* of the molded body measured using a D65 light source and an SCE method 10-degree field of view reflection mode of a painted product is about 1, it can be said that the jet blackness is the same as or greater than that of a painted product when L* is 1 or less. L* is an index that indicates the blackness of the molded product, and the closer it is to 0, the better the jet blackness. When L* is 1 or less, a molded product having excellent jet blackness can be obtained, and the appearance can be made to be less likely to look whitish even under outdoor light. L* is preferably 0.8 or less, and more preferably 0.5 or less. Usually, the L* of a resin molded product is 0.1 or more. When a black dye pigment and / or a combination of multiple dye pigments is used, L* can be adjusted by adjusting the amount and amount ratio of the black dye pigment and / or the combination of multiple dye pigments. As the dye, in order to improve the weather resistance of the methacrylic resin composition, anthraquinone dyes, heterocyclic compound dyes and perinone dyes are preferred. Note that L* can be measured by the method described in the examples below.

[0072] [Method for producing methacrylic resin composition] The above-mentioned methacrylic resin composition can be obtained, for example, by thoroughly mixing the methacrylic resin (A), the internal lubricant (B), the fatty acid amide (C), the dye (D) added as required, and other components by stirring, and then melt-kneading (compounding). Alternatively, the internal lubricant (B), the fatty acid amide (C), the dye (D), and other components are used to prepare a high-concentration master batch based on the methacrylic resin (A) by melt-kneading, and the master batch may be diluted with another methacrylic resin (A) and melt-kneaded.

[0073] Examples of the melt kneading method include a method of kneading and manufacturing using a kneader such as an extruder, a heating roll, a kneader, a roller mixer, or a Banbury mixer. Among these, kneading using an extruder is particularly preferred from the viewpoint of productivity, and a twin-screw extruder is more preferred than a single-screw extruder. The kneading temperature may be in accordance with the preferred processing temperature of the methacrylic resin (A), and is preferably 140 to 300°C, more preferably 180 to 280°C, and even more preferably 160 to 260°C. By setting the kneading temperature at 140°C or higher, stable processing with normal torque when operating the extruder tends to be possible. By setting the kneading temperature at 300°C or lower, the generation of residual monomers due to thermal decomposition of the methacrylic resin composition can be more effectively and reliably prevented, and the deterioration of physical properties such as heat resistance due to the plasticizing effect of the residual monomers and silver during injection molding tend to be more effectively and reliably prevented. The kneading temperature in this embodiment refers to the set temperature of the center of the cylinder when an extruder is used.

[0074] <Molded body> The molded article of the present embodiment contains the above-mentioned methacrylic resin composition of the present embodiment. The molded article of this embodiment can be manufactured by a known molding method. The known molding method is not limited to the following, but examples thereof include injection molding, extrusion molding, blow (hollow) molding, vacuum molding, compression molding, calendar molding, inflation molding, etc. In particular, it is preferable to make an extrusion molded article by extrusion molding (including multilayer extrusion molding) and to make an injection molded article by injection molding from the viewpoint of production efficiency, and it is more preferable to make an injection molded article by multilayer extrusion molding by heterogeneous multilayer extrusion molding with a different resin such as a polycarbonate resin used in the design surface surface layer of the methacrylic resin composition of the present invention, which has excellent scratch resistance, and molding by injection molding from the viewpoint of excellent scratch resistance and high appearance, and it is even more preferable to make an injection molded article by injection molding from the viewpoint of excellent scratch resistance and high appearance, as well as productivity and freedom of shape of the molded article. From the viewpoint of productivity, the molding temperature is preferably 170° C. or higher, more preferably 190° C. or higher, and even more preferably 200° C. or higher. From the viewpoint of preventing deterioration of the methacrylic resin (A) and volatilization of various additives, the molding temperature is preferably 290° C. or lower, more preferably 280° C. or lower, and even more preferably 260° C. or lower. From the viewpoint of productivity, the cylinder temperature during molding is preferably 170° C. or higher, more preferably 190° C. or higher, and even more preferably 200° C. or higher. From the viewpoint of preventing deterioration of the methacrylic resin (A) and volatilization of various additives and allowing the effects of each additive to be satisfactorily exhibited, the temperature is preferably 290° C. or lower, more preferably 280° C. or lower, and even more preferably 260° C. or lower.

[0075] (Thickness of molded body t) The thickness t of the molded body in this embodiment refers to the maximum value of the thickness (thickest part) of the flow cross section that appears when a molded body containing the methacrylic resin composition of this embodiment (hereinafter also referred to as a "molded body made of methacrylic resin composition") is cut perpendicular to the flow direction of the resin, excluding the original end part of the molded body. In the molded body, a leaf-vein-like channel structure may be partially provided to assist flow. The thickness t of the molded body made of the methacrylic resin composition in this embodiment does not refer to the thickness of the part having the channel structure, but rather to the thickness of the thickest part adjacent to the part having the channel structure other than the part having the channel structure. The molded article of this embodiment can be suitably used as a molded article having a thickness t of 1 to 5 mm, more suitably as an extrusion molded article or an injection molded article, and particularly suitably as an injection molded article. If the thickness exceeds 5 mm, the molding cycle time is lengthened to prevent appearance changes (so-called sink marks) due to thermal shrinkage, which tends to reduce productivity. The thickness t is more preferably 4 mm or less, and even more preferably 3 mm or less. If the thickness is less than 1 mm, the dwell pressure is not easily transmitted during injection molding, and the mold transferability at the flow end tends to deteriorate. The thickness t is more preferably 1.5 mm or more, and even more preferably 2 mm or more. If the thickness t is 3 mm or less, it can be said to be thin-walled.

[0076] (Length of molded body L) In this embodiment, the length L of the molded body refers to the maximum length (length to the farthest point) from the gate corresponding position (position corresponding to the gate of the mold) in the molded body. When two gates (gate 1 and gate 2) are used, the midpoint between gate 1 and gate 2 is defined as midpoint 1, and the longest length among the length from the farthest point U from midpoint 1 to the gate closest to location U, and the length from gate 1 or gate 2 to midpoint 1 is defined as length L. When three gates (gate 1, gate 2, and gate 3) are used, the midpoint between gate 1 and gate 2 is midpoint 1, the midpoint between gate 1 and gate 3 is midpoint 2, and the midpoint between gate 2 and gate 3 is midpoint 3, and the longest length among the length from midpoint 1 to the farthest location W to the gate closest to location W, the length from midpoint 2 to the farthest location X to the gate closest to location X, the length from midpoint 3 to the farthest location Y to the gate closest to location Y, the length from gate 1 or gate 2 to midpoint 1, the length from gate 1 or 3 to midpoint 2, and the length from gate 2 or gate 3 to midpoint 3 is the length L. The same definition is used when four or more gates are used. The midpoint between the gates and the length L can be measured along the surface of the molded body using an radius gauge, pin gauge, digital caliper, micrometer, etc. If the molded body is spherical or the like and has multiple midpoints, any one of them can be used as the midpoint to determine the farthest point and length L. From the viewpoint of reducing the occurrence of weld lines caused by the joining of resins and obtaining a molded product with a high appearance that utilizes jet blackness, L is preferably 130 mm or more, more preferably 150 mm or more, even more preferably 180 mm or more, even more preferably 190 mm or more, even more preferably 200 mm or more, and particularly preferably 320 mm or more. If L is 130 mm or more, it can be said to be a long molded product. There is no particular limit to the lower limit of L, but from the viewpoint of preventing deterioration of the resin due to a long residence time in the molding machine cylinder, 50 mm or more is preferable. In order to measure the length L, it is necessary to use a mold having a final filling portion therein.

[0077] (Ratio of the length L of the molded body to its thickness t, L / t) In order to prevent cracks from occurring in the molded body due to external forces applied to the molded body during molding or stresses generated when the molded body is placed, and in order to ensure that an appropriate holding pressure is applied in injection molding and that appearance defects such as silver streaks, sink marks, and weld lines can be effectively prevented, the ratio L / t of the length L to the thickness t is preferably 700 or less, more preferably 500 or less, and even more preferably 300 or less. Furthermore, in order to effectively prevent appearance defects such as sink marks and to obtain molded bodies with good productivity, the ratio is preferably 65 or more, more preferably 90 or more, even more preferably 110 or more, even more preferably 135 or more, and even more preferably 170 or more. In particular, the molded article of this embodiment has a thickness t of 1 to 5 mm and a length L of 130 mm or more, with L / t being preferably 65 or more, and L / t being more preferably 175 or more.

[0078] (Use of Molded Body) The molded article of the present embodiment can be suitably used in applications requiring scratch resistance.

[0079] The applications as mentioned above are not particularly limited, but can be used for example in furniture, household goods, storage and stockpiling items, building materials such as walls and roofs, toys and play equipment, hobby applications such as pachinko faces, medical and welfare products, office automation equipment, audio-visual equipment, battery electrical equipment, lighting equipment, body parts for ships and aircraft structures, vehicle parts, and the like, and can be particularly suitably used for vehicle applications such as body parts and vehicle parts, furniture applications, optical applications, and electrical and electronic applications. Examples of furniture applications include main bodies or decorative parts of chests, chairs, cabinets, cupboards, TV stands, living room cabinets, etc. Examples of optical applications include various lenses, touch panels, etc. In addition, in the fields of optical communication systems, optical switching systems, and optical measurement systems, they can also be used as waveguides, optical fibers, optical fiber coating materials, LED lenses, covers for lighting, etc. Examples of electrical and electronic applications include display devices such as personal computers, game machines, televisions, car navigation systems, and electronic paper, printers, copy machines, scanners, fax machines, electronic organizers and PDAs, electronic desk calculators, electronic dictionaries, cameras, video cameras, mobile phones, mice, numeric keypads, CD players, MD players, portable radios and audio players, etc. In particular, they can be suitably used for design parts of the housings of televisions, personal computers, game machines, car navigation systems, electronic paper, etc.

[0080] The molded article of the present embodiment is preferably a vehicle component, and is more preferably used as an interior or exterior component for an automobile, a peripheral portion of an automobile lamp, or a decorative material for an automobile. Examples of interior components for automobiles include meter covers, console boxes, center clusters, cup holders, and switch panels, while examples of exterior components for automobiles include headlamps and taillamps. Examples of decorative materials for the peripheral parts of automotive lamps include tail lamp garnishes, rear lamp garnishes, and front lamp garnishes. Examples of automotive design materials include automotive exterior design materials and automotive interior design materials. Automotive interior design materials include switch panels, instrument panels, and center clusters, while automotive exterior design materials include pillar garnishes, front grilles, rear grilles, license plate garnishes, rear garnishes, front garnishes, and emblems. From the viewpoint of more advantageously utilizing the effects of the present invention, automotive exterior design materials are preferred. In these applications, design is generally important, and automotive exterior design materials in particular are thin-walled, long parts. EXAMPLES

[0081] [Raw materials used in the examples and comparative examples] <Raw material for methacrylic resin (A)> The raw materials of the methacrylic resin (A) used in the production of the methacrylic resin composition are as follows. Methyl methacrylate (MMA): Asahi Kasei (containing 2.5 ppm by mass of 2,4-dimethyl-6-t-butylphenol manufactured by Chugai Boeki as a polymerization inhibitor) Methyl acrylate (MA): manufactured by Mitsubishi Chemical (containing 14 ppm by mass of 4-methoxyphenol manufactured by Kawaguchi Chemical Industry Co., Ltd. as a polymerization inhibitor) n-Octyl mercaptan: Arkema Lauroyl peroxide: NOF Corporation - Tribasic calcium phosphate: Manufactured by Nippon Chemical Industry Co., Ltd., used as a suspending agent Calcium carbonate: Shiraishi Kogyo Co., Ltd., used as a suspending agent Sodium lauryl sulfate: Manufactured by Wako Pure Chemical Industries, used as a suspension aid

[0082] <Internal Lubricant (B)> B-1: NAA-45 (Stearyl alcohol): NOF Corporation B-2: NAA-42 (Lauryl alcohol): NOF Corporation B-3: Butyl stearate: NOF Corporation B-4: Calcium stearate: NOF Corporation

[0083] <Fatty acid amide (C)> C-1: Alflow S10 (stearic acid amide): NOF Corporation C-2: BNT-22H (behenic acid amide): manufactured by Nippon Fine Chemicals C-3: Neutron (oleic acid amide): made by Nippon Fine Chemicals C-4: Neutron-S (erucic acid amide): manufactured by Nippon Fine Chemicals C-5: Kao Wax EB-FF (EBS): Made by Kao

[0084] <Dye (D)> D-1: Macrolex Green G (anthraquinone dye): maximum absorption wavelength 685 nm in the wavelength range of 400 nm to 780 nm D-2: Plast Blue 8520 (anthraquinone dye): maximum absorption wavelength 580 nm in the wavelength range of 400 nm to 780 nm D-3: Macrolex Violet 3R (anthraquinone dye): maximum absorption wavelength 560 nm in the wavelength range of 400 nm to 780 nm

[0085] <Other ingredients> Tegomer H-Si6441P (additive): Silicone additive made by Evonik Metablen S2260 (impact resistance agent): graft copolymer containing silicone components · Ingeo2500HP (refractive index modifier): polylactic acid polymer

[0086] [Measurement and evaluation method] <Measurement of molecular weight of methacrylic resin (A)> The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) (Mn is number average molecular weight) of the methacrylic resin (A) were measured using the following device and under the following conditions. Measurement equipment: Tosoh Corporation gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were connected in series. With this column, high molecular weight molecules elute early, and low molecular weight molecules elute slowly. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Column temperature: 40℃ Sample: 0.02 g of methacrylic resin in 20 mL of tetrahydrofuran Injection volume: 10μL Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min, 2,6-di-t-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard. As standard samples for the calibration curve, the following ten types of polymethyl methacrylate (Polymer Laboratories; PMMA Calibration Kit M-M-10) with known monodisperse peak molecular weights and different molecular weights were used. In addition, since the polymethyl methacrylates of the standard specimens used for the standard samples for the calibration curve each had a single peak, the corresponding peaks were expressed as weight peak molecular weights Mp, which was distinguished from the peak top molecular weights calculated when a sample had multiple peaks. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard material 10 850 Under the above conditions, the RI detection intensity was measured against the elution time of the methacrylic resin (A). Based on the area in the GPC elution curve and the calibration curve of the third order approximation, the weight average molecular weight (Mw) and the molecular weight distribution (Mw / Mn) of the methacrylic resin (A) were calculated. In addition, the peak top molecular weight (Mp) in the GPC elution curve was calculated from the GPC elution curve and the calibration curve, and the content of the molecular weight component of 1 / 5 or less of Mp was calculated as follows. First, the area in the GPC elution curve of the methacrylic resin (A) was obtained. Next, the area in the GPC elution curve was divided by the elution time corresponding to a molecular weight of 1 / 5 of Mp, and the area in the GPC elution curve corresponding to a molecular weight component of 1 / 5 or less of Mp was obtained. The ratio of the area to the area in the GPC elution curve was used to determine the proportion of components with molecular weights of 1 / 5 or less of Mp.

[0087] <Analysis of the structural unit of methacrylic resin (A)> 1 The structural units were identified by H-NMR measurement, and their amounts (parts by mass) were calculated. 1 The measurement conditions for H-NMR measurement are as follows. Equipment: JEOL-ECA500 Solvent: CDCl3-d1 (deuterated chloroform) Sample: 1 g of methacrylic resin (A) was dissolved in 10 ml of acetone, 20 ml of methanol was added dropwise, and the solution was filtered. The insoluble matter was vacuum dried at 40°C for 15 hours, and 15 mg of the insoluble matter was dissolved in 10.75 mL of CDCl3-d to prepare a sample for measurement.

[0088] <Measurement of mass proportion b of internal lubricant (B) and mass proportion c of fatty acid amide (C) contained in methacrylic resin (A)> The mass proportion of the internal lubricant (B) contained in the methacrylic resin was measured by a calibration curve method using the GC apparatus and conditions described below, and the mass proportion b (parts by mass) of the internal lubricant (B) in the methacrylic resin (A) and the mass proportion c (parts by mass) of the fatty acid amide (C) were calculated. Measuring device: Shimadzu Corporation GC-2025 GASCHROMATOGRAPH Column: Phenomenex Zebron ZB-1 (column length 30 m, column diameter 0.32 mm) Column temperature: After maintaining at 100° C. for 3 minutes, the temperature was increased to 300° C. at a rate of 10° C. / min and maintained at that temperature for 5 minutes. Detector: FID (300℃) Measurement sample preparation: 0.3 g was dissolved in 15 mL of chloroform, and 2 mL of internal standard solution was added and the volume was adjusted to 25 mL. Sample injection volume: 1μL

[0089] <Evaluation of jet blackness> The lightness L* of a 3 mm thick plate sample obtained by the method described below was measured using a Konica Minolta spectrophotometer CM-700d with a D65 light source, SCE method, 10 degree visual field reflection mode, and a measurement diameter of φ11 mm. The jet-blackness was evaluated as follows: if L* was 0.5 or less, it was "◎" (excellent); if it was more than 0.5 and less than 0.8, it was "◯" (good); if it was more than 0.8 and less than 1, it was "△" (practical); and if it was more than 1, it was "×" (poor).

[0090] <Evaluation of scratch resistance> Using the injection molded flat plate samples obtained in the examples and comparative examples, a car wash towel (economy car wash towel (cotton): Joyfull Co., Ltd.) was set on the tip of a 2 cm square 45R (curved surface radius 45 mm) jig of a Gakushin type friction tester (Daiei Scientific Instruments Manufacturing Co., Ltd., RT-200), and the surface of the jig that comes into contact with the evaluation sample was covered with the car wash towel as shown in Figure 1. The car wash towel was fixed so that it would not slip, and slid back and forth 100 times in the direction perpendicular to the flow direction of the resin under the conditions of a load of 1 kgf, a test distance of 120 mm, and a reciprocating speed of 12 reciprocations / min. The lightness L* was measured before and after the scratch resistance test, and ΔL* was calculated. ΔL* = L* after scratch resistance test - L* before scratch resistance test In addition, the surface of the molded product after the scratch resistance test was visually observed, and the scratch resistance was evaluated according to the following evaluation criteria. ◎ (Excellent): ΔL* is 0.1 or less, and wear marks are almost invisible. ○ (Good): ΔL* is greater than 0.1 and less than 0.2, and slight wear marks are visible. △ (sufficient for practical use): ΔL* is greater than 0.2 and less than 0.3, and wear marks are slightly visible. △△ (Practical): ΔL* is greater than 0.3 and less than 0.65, and wear marks are visible. × (poor): Over 0.65, wear marks are clearly visible. When ΔL* was 0.1 or less, the wear marks could not be visually recognized and the scratch resistance was excellent. When ΔL* was more than 0.1 and less than 0.2, the wear marks were only slightly visually recognized and the scratch resistance was good. When ΔL* was more than 0.2 and less than 0.3, the wear marks were slightly visible but were practically sufficient. When ΔL* was more than 0.3 and less than 0.65, the wear marks were visible but were practically sufficient. When ΔL* was more than 0.65, the wear marks were fully visible and the scratch resistance was poor. As for the evaluation of scratch resistance immediately after molding, the same evaluation was carried out within one hour after injection molding of the flat plate sample.

[0091] <Strength evaluation> Dumbbell test pieces were molded using the resin pellets obtained in the Examples and Comparative Examples described below, and the tensile stress (MPa) was measured as an index for strength evaluation in accordance with ISO 527. The tensile speed was 5 mm / min, and the dumbbell test pieces were annealed at 75°C for 16 hours and then conditioned at 23°C and 50% RH for 24 hours. The strength was evaluated as follows: if the tensile strength was 75 MPa or more, it was designated as "◎" (excellent); if it was 73 MPa or more but less than 75 MPa, it was designated as "〇" (good); if it was 70 MPa or more but less than 73 MPa, it was designated as "△" (practical); and if it was less than 70 MPa, it was designated as "×" (poor).

[0092] <Evaluation of heat deformation resistance> Dumbbell test pieces were molded using the resin pellets obtained in the Examples and Comparative Examples described below, and the VICAT softening temperature (°C) was measured in accordance with ISO306B50 to be used as an index for evaluating heat distortion resistance. The test pieces were dried under reduced pressure at 75°C for 16 hours. Heat deformation resistance was evaluated as follows: if the VICAT softening temperature was 103°C or higher, it was marked as "◎" (excellent); if it was 95°C or higher but less than 103°C, it was marked as "〇" (good); if it was 90°C or higher but less than 95°C, it was marked as "△" (practical); and if it was less than 90°C, it was marked as "×" (poor).

[0093] <Evaluation of fluidity and flow stability> Dumbbell test pieces prepared by the method described below were crushed into small pieces using nippers or the like, and dried at 80°C under reduced pressure for 24 hours to prepare measurement samples. Using the measurement samples, the fluidity was evaluated by measuring the average MFR (g / 10 min) of the second to sixth samples under conditions based on JIS K7210:1999, a load of 3.8 kgf, a test temperature of 230°C, a preheating time of 4 minutes, and sampling every 30 seconds. In addition, the flow stability was evaluated based on the absolute difference in MFR between the sixth and second samples measured under the same conditions.

[0094] <Evaluation of light shielding properties when coloring thin-walled molded pieces> The spectral transmittance from 400 nm to 780 nm of a 3 mm thick flat plate sample obtained by the method described below was measured using a Shimadzu UV2600 spectrophotometer. The light shielding ability when coloring the thin-walled molded piece was evaluated as follows: if the wavelength at which the transmittance reached 5% was 650 nm or more, it was judged as "◯" (good); if it was 550 nm or more, it was judged as "△" (practical); and if it was less than 550 nm, it was judged as "×" (poor). Sampling pitch: 1 nm Slit width: 5 nm Scan speed: Medium

[0095] <Transparency evaluation> The resin pellets obtained in the Examples and Comparative Examples were used to mold flat plate samples by the method described below, and the total light transmittance (%) was measured at a temperature of 23° C. to evaluate transparency. The total light transmittance was measured using a Nippon Denshoku Industries Co., Ltd. model NDH7000SP instrument according to the ISO13468-1 standard. If the total light transmittance is 92% or more, it is "◎" (excellent); if it is between 91% and 92%, it is "〇" (good); if it is between 90% and 91%, it is "△" (practical); if it is less than 90%, it is "〇" (good). If so, the transparency was evaluated as "x" (poor).

[0096] <Evaluation of turbidity> The resin pellets obtained in the Examples and Comparative Examples were molded into flat plates by the methods described below, and the haze value (%) was measured at a temperature of 23° C. to evaluate the turbidity. The haze value was measured using a Nippon Denshoku Industries Co., Ltd. NDH7000SP instrument by a transmission measurement method conforming to the ISO14782 standard. Turbidity was evaluated as follows: if the haze value was 0.5% or less, it was "◎" (excellent); if it was between 0.5% and 0.8%, it was "〇" (good); if it was between 0.8% and 1% it was "△" (usable); and if it was over 1%, it was "×" (poor).

[0097] <Evaluation of formability of thin-walled and long molded bodies with joints> When molding a thin-walled, long molded product obtained by the method described below, with a length L of 470 mm, a thickness t of 2.5 mm, and a ratio L / t of 188, the product had a joint (female snap fit) in the center of the molded product with outer dimensions of 10 mm × 10 mm, inner dimensions of 8 mm × 8 mm, a height of 3 mm, and a structure with a claw part of 1 mm × 1 mm × 0.5 mm on the inside, as shown in Figure 2. The product was evaluated for the occurrence of appearance defects such as cracks, sink marks, and flow marks. The evaluation was performed by visual judgment. Five thin, long molded bodies having joints obtained by the method described below were molded, and if even one of them had a defective appearance, it was judged to have a defective appearance.

[0098] [Methacrylic resin composition] The methacrylic resin (A) used as a constituent component of the methacrylic resin composition in the examples and comparative examples described later will be described below.

[0099] <Methacrylic resin (A)> As the methacrylic resin (A), a methacrylic resin (A-1) produced in accordance with the following Production Example A1 was used.

[0100] (Production Example A1 (Production of Methacrylic Resin (A-1))) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of ion-exchanged water was added to a 60 L reactor, and the temperature was raised to 80° C., and then mixed liquid (a), 21.0 kg of methyl methacrylate, 0.65 kg of methyl acrylate, 26 g of lauroyl peroxide, and 54 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80° C., and after observing an exothermic peak, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C and 20 parts by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles. The obtained polymer microparticles were melt-kneaded in a φ26 mm twin-screw extruder set at 240°C, and the strands were cooled and cut to obtain resin pellets [methacrylic resin (A-1)]. The weight-average molecular weight of the obtained resin pellets was 108,000, the peak top molecular weight (Mp) was 115,000, and the molecular weight distribution (Mw / Mn) was 1.85. Furthermore, the abundance (%) of molecular weight components with a value of 1 / 5 or less of the Mp value was 4.5%. The structural unit was MMA / MA=98 / 3 (parts by mass).

[0101] (Production Example A2 (Production of Methacrylic Resin (A-2))) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of ion-exchanged water was added to a 60 L reactor, and the temperature was raised to 80° C., and then mixed liquid (a), 20.6 kg of methyl methacrylate, 1.1 kg of methyl acrylate, 39 g of lauroyl peroxide, and 34 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80° C., and after observing an exothermic peak, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C and 20 parts by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles. The obtained polymer microparticles were melt-kneaded in a φ26 mm twin-screw extruder set at 240°C, and the strands were cooled and cut to obtain resin pellets [methacrylic resin (A-2)]. The weight-average molecular weight of the obtained resin pellets was 160,000, the peak top molecular weight (Mp) was 167,000, and the molecular weight distribution (Mw / Mn) was 1.85. Furthermore, the abundance (%) of molecular weight components with a value of 1 / 5 or less of the Mp value was 4.5%. The structural unit was MMA / MA=95 / 5 (parts by mass).

[0102] (Production Example A3 (Production of Methacrylic Resin (A-3)) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of ion-exchanged water was added to a 60 L reactor, and the temperature was raised to 70° C., and then mixed liquid (a), 16.2 kg of methyl methacrylate, 5.4 kg of methyl acrylate, 26 g of lauroyl peroxide, and 54 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 70° C., and after observing an exothermic peak, the temperature was raised to 85° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C and 20 parts by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles. The obtained polymer microparticles were melt-kneaded in a φ26 mm twin-screw extruder set at 240°C, and the strands were cooled and cut to obtain resin pellets [methacrylic resin (A-3)]. The weight-average molecular weight of the obtained resin pellets was 108,000, the peak top molecular weight (Mp) was 115,000, and the molecular weight distribution (Mw / Mn) was 1.85. Furthermore, the abundance (%) of molecular weight components with a value of 1 / 5 or less of the Mp value was 4.5%. The structural unit was MMA / MA=80 / 20 (parts by mass).

[0103] (Production Example A4 (Production of Methacrylic Resin (A-4)) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of ion-exchanged water was put into a 60 L reactor, and the temperature was raised to 80° C., and then the mixed liquid (a), 21.7 kg of methyl methacrylate, 26 g of lauroyl peroxide, and 52 g of n-octyl mercaptan were put into the reactor. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80° C., and after observing an exothermic peak, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C and 20 parts by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles. The obtained polymer microparticles were melt-kneaded in a φ26 mm twin-screw extruder set at 240°C, and the strands were cooled and cut to obtain resin pellets [methacrylic resin (A-4)]. The weight-average molecular weight of the obtained resin pellets was 110,000, the peak top molecular weight (Mp) was 115,000, and the molecular weight distribution (Mw / Mn) was 1.85. Furthermore, the abundance (%) of molecular weight components with a value of 1 / 5 or less of the Mp value was 4.5%. The structural unit was MMA 100 (parts by mass).

[0104] [Examples 1 to 39] [Comparative Examples 1 to 14] The methacrylic resin (A), internal lubricant (B), fatty acid amide (C), dye (D) and other additives were weighed out so as to obtain the blending ratios shown in Tables 1 and 2, and then mixed and dispersed by dry blending. After thorough mixing, the mixed raw materials were fed into a twin-screw extruder of φ26 mm, melt-kneaded (compounded) to generate strands, cooled in a water bath, and cut with a pelletizer to obtain pellets. During compounding, a vacuum line was connected to the vent of the extruder, and volatile components such as moisture and monomer components were removed under conditions of -0.06 MPa. Thus, a methacrylic resin composition was obtained. The temperature of the resin composition during compounding was 240°C. The numerical values ​​in Tables 1 to 4 represent the number of blended parts (parts by mass) when the mass of the methacrylic resin (A) is 100 parts by mass.

[0105] <Plate sample> (injection molding) The obtained pellets of the methacrylic resin composition were put into a 100t class injection molding machine (Shibaura Machine EC-100SX) and molded into a 100 mm square plate with a thickness of 3 mm to prepare a plate sample for evaluation. The mold used had its surface (mold cavity inner surface) polished with 8000 grit sandpaper. The molding conditions for the evaluation plate samples were set as follows. Molding temperature (cylinder temperature): 260℃ Mold temperature: 60℃ Also, it is important to keep the mold temperature high during injection molding in order to improve the transferability of the mold surface that has been polished with 8000 grit sandpaper, but if the mold temperature is too high, the cooling time will be too long and it will become impractical. The mold temperature range that ensures these good results is between 40°C and 100°C, more preferably between 50°C and 90°C, and this time we selected 60°C.

[0106] (injection molding) The obtained pellets of the methacrylic resin composition were fed into a 650t class injection molding machine (EC-650SXIII manufactured by Shibaura Machine) to form a molded article as shown in Figure 2, which had a length L: 470 mm, a thickness t: 2.5 mm, a length L to thickness t ratio L / t: 188, and a joint (female snap fit) in the center of the molded article with outer dimensions of 10 mm x 10 mm, inner dimensions 8 mm x 8 mm, and a height of 3 mm, and a structure with a claw portion of 1 mm x 1 mm x 0.5 mm on the inside. The molding temperature for the thin, long molded body having this joint was set as follows: Molding temperature (cylinder temperature): 260℃ Mold temperature: 80℃ Filling speed: 12.7cm 3 / sec

[0107] <Dumbbell test piece> (injection molding) The pellets of the obtained methacrylic resin composition were put into an injection molding machine (Shibaura Machine EC-100SX) to mold a type 1A dumbbell test piece as a sample for evaluation. The molding conditions were in accordance with ISO8257-2. The filling speed was 10 cm 3 / second.

[0108] [Table 1]

[0109] [Table 2]

[0110] [Table 3]

[0111] [Table 4]

[0112] As shown in Tables 1 to 4, in Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37), methacrylic resin compositions were produced that had excellent transparency, turbidity, scratch resistance, scratch resistance immediately after molding, strength, heat distortion resistance, and jet black color when colored black. In Example 1 (Example 20), the scratch resistance and scratch resistance immediately after molding were slightly inferior to those in Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37), although the level was practically acceptable. This is believed to be because the amount of fatty acid amide (C) added was smaller and the b / c ratio was larger than those in Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37). In Example 2 (Example 21), the scratch resistance immediately after molding was somewhat inferior to Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37), although it was at a practical level. This is believed to be because b / c was larger than in Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37). In Example 3 (Example 22), the scratch resistance immediately after molding was somewhat inferior to Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37), although it was at a practically sufficient level. This is believed to be because b / c was larger than in Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37). In Example 9 (Example 28), the jet blackness and heat resistance were slightly inferior to Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37) although they were at a practically sufficient level, and the scratch resistance immediately after molding was slightly inferior, although it was at a practically acceptable level. This is believed to be because the amount of fatty acid amide (C) added was larger than in Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37), and the b / c ratio was smaller. In Example 11 (Example 30), the scratch resistance immediately after molding was somewhat inferior to Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37), although it was at a practically sufficient level. This is believed to be because b / c was larger than in Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37). In Example 12 (Example 31), the tensile strength was slightly inferior to Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37) although it was at a practically sufficient level, and the scratch resistance immediately after molding was slightly inferior, although it was at a practically acceptable level. This is believed to be because the amount of internal lubricant (B) added was larger than in Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37), and the b / c ratio was larger. In Example 19 (Example 38), the jet blackness was slightly inferior to Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37) although it was at a practically sufficient level, and the scratch resistance and scratch resistance immediately after molding were slightly inferior, although they were at a practically acceptable level. This is believed to be because the fatty acid amide has a larger carbon number than Examples 4 to 8 (Examples 23 to 27), 10 (Example 29), and 13 to 18 (Examples 32 to 37), and the structure does not have an amide group at the molecular terminal. In Comparative Example 1 (Comparative Example 8), since no internal lubricant was included, the residual stress in the surface of the molded product was large, and the scratch resistance was insufficient, so that the subsequent evaluations were not carried out. In Comparative Example 2 (Comparative Example 9), since no fatty acid amide was contained, the surface of the molded article had insufficient slipperiness and insufficient scratch resistance, and the subsequent evaluations were not carried out. In Comparative Example 3 (Comparative Example 10), the b / c ratio was too small, and therefore the scratch resistance was insufficient, and the subsequent evaluations were not carried out. In Comparative Example 4 (Comparative Example 11), since no internal lubricant was contained, and instead an organically modified silicone was contained, the haze and jet black properties were insufficient, and the subsequent evaluations were not carried out. Comparative Example 5 (Comparative Example 12) did not contain an internal lubricant, and instead contained an acrylic rubber or a polylactic acid polymer, so that the total light transmittance, haze, and jet blackness were insufficient, and the subsequent evaluations were not carried out. In Comparative Example 6 (Comparative Example 13), the content of methyl methacrylate monomer units contained in the methacrylic resin (A) was low, and therefore the heat resistance was insufficient, and the following evaluations were not carried out. In Examples 21, 24, and 25, the absolute value of the difference in MFR between the sixth and second samples was 0.2 or less, and the flow stability was good. In Examples 20 and 25 and Comparative Examples 8, 9, 10, and 14, thin-walled, long molded bodies having joints were injection molded under the above conditions. As a result, good molded bodies were obtained in Examples 20 and 25, but in Comparative Examples 9 and 14, the fluidity was insufficient, causing cracks or flow marks, and in Comparative Examples 8 and 10, the amount of internal lubricant (B) added was small, and the b / c ratio was small, causing sink marks on the design surface behind the snap fit, making it impossible to obtain a molded body with a good appearance. In Examples 20 and 25, the wavelength at which the transmittance of a 3 mm thick flat sample reached 5% in the range of 400 nm to 780 nm was 650 nm or more, which was a good level, while in Example 39 it was 550 nm or more, which was a practical level. [Industrial Applicability]

[0113] According to the methacrylic resin composition of the present invention, it is possible to produce a methacrylic resin composition which, when molded into a molded article, has excellent transparency, turbidity, and scratch resistance, and has jet black color when colored black, and therefore has the potential for industrial use as vehicle components, home appliance components, and miscellaneous goods.

Claims

1. The composition comprises a methacrylic resin (A), an internal lubricant (B), and a fatty acid amide (C), The content of the methacrylic acid ester monomer unit in the methacrylic resin (A) is more than 85 parts by mass and 99.9 parts by mass or less, The internal lubricant (B) is one or more compounds selected from the group consisting of aliphatic alcohols, aliphatic alkyls, metal soaps, fatty acids, and liquid paraffin; a mass ratio b of the internal lubricant (B) is 0.05 to 0.6 parts by mass, and a mass ratio c of the fatty acid amide (C) is 0.5 to 6 parts by mass, relative to 100 parts by mass of the methacrylic resin (A), and the mass ratio b (parts by mass) and the mass ratio c (parts by mass) satisfy the following formulas (i) and (ii): A methacrylic resin composition comprising: 0.025≦b / c≦0.3...(i) c+b≦6.15...(ii)

2. 2. The methacrylic resin composition according to claim 1, wherein the methacrylic acid ester monomer units in the methacrylic resin (A) are methyl methacrylate monomer units.

3. The methacrylic resin composition according to claim 2, wherein the internal lubricant (B) is an aliphatic alcohol having 12 to 22 carbon atoms.

4. The methacrylic resin composition according to claim 3, wherein the aliphatic amide (C) comprises at least one aliphatic amide having 16 to 24 carbon atoms.

5. 5. The methacrylic resin composition according to claim 4, wherein when a molded article having a thickness of 3 mm is molded using a mold having a polishing number of 8000 at a molding temperature of 260°C and a mold temperature of 60°C, the lightness L* of the molded article is 1 or less, as measured using a D65 light source, SCE method, and a 10-degree visual field reflection mode.

6. The methacrylic resin composition according to claim 5, further comprising a dye (D) containing at least one dye selected from the group consisting of red dyes, yellow dyes, green dyes, blue dyes, and violet dyes.

7. The methacrylic resin composition according to claim 6, wherein the dye (D) comprises one or more dyes selected from the group consisting of anthraquinone dyes, heterocyclic compound dyes, and perinone dyes.

8. The methacrylic resin composition according to claim 7, having a Vicat softening temperature of 95 to 108°C according to ISO306 B50 method.

9. 9. The methacrylic resin composition according to claim 8, wherein the average melt mass-flow rate (MFR) of second to sixth samples taken every 30 seconds at 230°C, a load of 3.8 kgf, and a pre-heating time of 4 minutes is 2.4 to 8.0 g / 10 min, and the absolute value of the difference in MFR between the sixth sample and the second sample is less than 0.2 g / 10 min.

10. A molded article comprising the methacrylic resin composition according to claim 9.

11. The molded article according to claim 10, which is a vehicle component.

Citation Information

Patent Citations

  • Thermoplastic resin composition, molded article, and vehicle material

    WO2018016473A1

  • Resin composition and molded article thereof

    WO2022085801A1